Here's the question you clicked on:
kshoaf
how does (sec^2(x)-1)/(sec^2(x))=1-cos^2(x)
lol thanks im thinking to hard
First, split the left-side fraction into two: (sec^2(x)-1)/(sec^2(x))=1-cos^2(x) (sec^2(x)/(sec^2(x) - 1/(sec^2(x)) = 1 - cos^2(x) Then, simplify the first item to 1: (sec^2(x)/(sec^2(x) - 1/(sec^2(x)) = 1 - cos^2(x) 1 - 1/(sec^2(x)) = 1 - cos^2(x) Lastly, simplify sec^2(x) into cosine: 1 - 1/(sec^2(x)) = 1 - cos^2(x) 1 - cos^2(x) = 1 - cos^2(x) And it's equal.
@kshoaf : LOL... pleasure :)
thinking hard is not to good for health ;)
not at all...especially with a final tomorrow. How am I supposed to do the hard stuff when I'm over thinking the simple steps
aw... you will ace it :) dont worry
the best thing to do before a maths test is relax :D